A multi‐parent advanced generation inter‐cross (MAGIC) population for genetic analysis and improvement of cowpea (Vigna unguiculata L. Walp.). (24th February 2018) - Huynh, Bao‐Lam; Ehlers, Jeffrey D.; Huang, Bevan Emma; Muñoz‐Amatriaín, María; Lonardi, Stefano; Santos, Jansen R. P.; Ndeve, Arsenio; Batieno, Benoit J.; Boukar, Ousmane; Cisse, Ndiaga; Drabo, Issa; Fatokun, Christian; et al.
Summary: Multi‐parent advanced generation inter‐cross (MAGIC) populations are an emerging type of resource for dissecting the genetic structure of traits and improving breeding populations. We developed a MAGIC population for cowpea ( Vigna unguiculata L. Walp.) from eight founder parents. These founders were genetically diverse and carried many abiotic and biotic stress resistance, seed quality and agronomic traits relevant to cowpea improvement in the United States and sub‐Saharan Africa, where cowpea is vitally important in the human diet and local economies. The eight parents were inter‐crossed using structured matings to ensure that the population would have balanced representation from each parent, followed by single‐seed descent, resulting in 305 F8 recombinant inbred lines each carrying a mosaic of genome blocks contributed by all founders. This was confirmed by single nucleotide polymorphism genotyping with the Illumina Cowpea Consortium Array. These lines were on average 99.74% homozygous but also diverse in agronomic traits across environments. Quantitative trait loci (QTLs) were identified for several parental traits. Loci with major effects on photoperiod sensitivity and seed size were also verified by biparental genetic mapping. The recombination events were concentrated in telomeric regions. Due to its broad genetic base, this cowpea MAGIC population promises breakthroughs in genetic gain, QTL and gene discovery, enhancement of breeding populations and, for some lines, direct releases as new varieties. Significance Statement: This paper reports the development and analysis of a multi‐parent population of the warm‐season legume cowpea, a crop of vital importance in global food security, providing a foundation for breakthroughs in genetic gain and quantitative trait locus (QTL) discovery. In particular, the QTL detected for photoperiod sensitivity will further our understanding of the genetics of flowering time in the photoperiod‐sensitive cowpea and related species.